RESEARCH IS NOT ALWAYS RE-SEARCH: A JOURNEY FROM BASICS TO ACIDIC (Journal of Forensic Medicine & Toxicology, 2024)
Research can be viewed from different levels. In a general way, it is a search for information and knowledge. Understanding research at the primary level is getting answers to specific questions. In our day-to-day life, we ask questions to ourselves or to others to attain some information. For example, we may have to go somewhere and suddenly find closure of the road ahead. At that moment, we first start to think that it may be because of an accident, a technical issue in a vehicle in the middle of the road, public agitation or political pressure, etc, then we probe further to reach the actual cause. In this short action, we become busy observing, forming hypotheses, testing, and concluding1. This way, research is not always high-sounding, technical, complex, and involves statistics or computers. It is a process of finding out the answer to the question in mind.
Keywords: professionals; academic